Microwave-assisted in situ laser dye incorporation into high sensitivity whispering gallery mode microresonators. (26th October 2021) - Mondragón-Ochoa, Jesús S; González-Rivera, José; Toparli, Cigdem; Khanum, Rizwana; Moirangthem, Rakesh S; Duce, Celia; Ferrari, Carlo; Barillaro, Giuseppe; Erbe, Andreas
Abstract: Optical whispering gallery mode microresonators (WGM- µ Rs) are powerful sensitive components with many analytical applications. Here, spherical WGM- µ Rs have been synthesised in a single-step microwave (MW)-assisted heterophase polymerisation. The microresonators are based on poly(styrene) beads into which the organic lasing dye nile red was incorporated as gain medium in situ during the polymerisation. The particle diameter and diameter distribution of the synthesised particles were tuned in the range of around 200 nm up to 50 µ m by adjusting the concentration between stabiliser poly-( N -vinyl pyrrolidone) (PVP) and monomer styrene, and the solvent composition in the dispersion process. Lower water content enabled the synthesis of spherical particles with large size polydispersity, from which WGM- µ Rs with a variety of diameters were selected. Microspheres with diameters ≳ 3.5 μ m supported WGMs. The WGMs were excited through free space via the fluorescence of the laser dye. Pumping power levels < 1 µ W were sufficient to excite WGMs. WGM shifts of beads with diameter between ≍5 and 30 µ m measured in air and water show a sensitivity up to 54 nm/RIU for the smallest particles. Dye doped WGM- µ R in the low µ m size range obtained by the MW-assisted polymerisation process with its versatility, low processing times and high yields opens new horizons for the applications of these systems as sensors.